(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
There is a family of complexes defined by the generic formula, and the arene moiety isconsidered the most important component of this family. By controlling the concentration of electrons inthe central atoms and keeping Ru in its 2+ oxidation state, it serves a crucial role in ensuring thecomplexes’ stability. RuII drug transport across cell membrane and interactions with potential targetsmay be facilitated by hydrophobic faces offered by more prolonged coordinated arenes such as biphenylor tetrahydroanthracene. Experiments have demonstrated that larger arenes in complexeshave more cytotoxic action. In this paper review the structural characteristics for anticancer activity of ru(ii) arene complexes.